Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2466/pr0.94.1.67-76
|View full text |Cite
|
Sign up to set email alerts
|

Sociotropy—Autonomy and Situation-Specific Anxiety

Abstract: Sociotropy and autonomy are conceptualized as two personality dimensions that relate to individuals' vulnerability to anxiety and depression. Sociotropy is characterized as an excessive investment in interpersonal relationships, and autonomy is characterized as an excessive concern with independence as well as a lack of concern for others. The present study investigated the relationships between sociotropy-autonomy and trait anxiety associated with four types of situations, i.e., Social Evaluation, Physical Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
2
5
0
5
Order By: Relevance
“…As found commonly in previous research (e.g. Clark & Oates, 1995; Clark et al , 1995; Robins et al , 1995; Sato & McCann, 1997; Sato, McCann, & Ferguson‐Isaac, 2004), there was a positive correlation between one's own level of sociotropy and one's own level of autonomy among both females and males. As hypothesized, there was also a positive correlation between one's own level of sociotropy and one's own level of RM for both males and females.…”
Section: Resultssupporting
confidence: 85%
“…As found commonly in previous research (e.g. Clark & Oates, 1995; Clark et al , 1995; Robins et al , 1995; Sato & McCann, 1997; Sato, McCann, & Ferguson‐Isaac, 2004), there was a positive correlation between one's own level of sociotropy and one's own level of autonomy among both females and males. As hypothesized, there was also a positive correlation between one's own level of sociotropy and one's own level of RM for both males and females.…”
Section: Resultssupporting
confidence: 85%
“…It is possible that some elements of autonomous personality, such as the ability to cope independently in the absence of social support, may provide a protective function during the transition from pregnancy to postpartum, whereas other aspects, such as the need for control and time for oneself, may increase the risk of depression during this period. Future studies should attempt to unravel the complexities regarding to construct of autonomous personality in order to clarify those aspects are associated with mental health outcomes (Sato & McCann, 2000;Sato, McCann, & Ferguson-Isaac, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…With respect to depression, although there is no direct theoretical insight into the relationship between FNE and depression, empirical data have revealed moderate correlations between FNE and depression (Collins et al, 2005;Duke, Krishnan, Faith, & Storch, 2006;Kocovski & Endler, 2000;O'Connor, Berry, Weiss, & Gilbert, 2002;Sato, McCann, & Ferguson-Isaac, 2004). Some indirect evidence has suggested that symptoms of depression are related to the fear of rejection, disapproval, and criticism (Clark, Steer, Haslam, Beck, & Brown, 1997;Sato, 2003).…”
Section: Fear Of Negative Evaluationmentioning
confidence: 93%